Dynamika Przekładki Hipoidalnej do Napędu Pojazdów Szynowych - Kamiński, E.; Nadolski, W. (Engineering Transactions, 1972)
In the paper is analyzed the mechanical model of a hypoidal gear with continuously distributed parameters. On the basis of a discrete model are determined the dynamic reactions acting between the teeth under the following assumptions: 1) no impact occurs between the teeth; 2) deformation of the shafts and their supports do not influence the deformation of the teeth. The free torsional vibration frequencies of the system are determined from the model characterized by continuously distributed parameters.